PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PASAR PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2014-2018 - nurul azizah (Universitas Muhammadiyah Tangerang, 2020)
ABSTRACT The purpose of this research is to know the effect of Intellectual Capital on market performance partially and together at Property and Real Estate company listed on the Indonesia Stock Exchange (IDX). The population in this study is the Property and Real Estate sector companies that are listed on the Indonesia Stock Exchange in 2014-2018. With a total sample of 39 companies taken by purposive sampling. The research variable consists of dependent variables is market performance and independent variables is intellectual capital which is proxied with human capital efficiency, structural capital efficiency and capital employed efficiency. The research method used is descriptive statistical method. The analysis used is multiple linear regression analysis to determine the intellectual capital equation both simultaneously and partially to market performance helping by IBM SPSS Statistics 20. The results of this study indicate that human capital efficiency and structural capital efficiency does not affect market performance, while capital employed efficiency has a positive effect on market performance. Keywords: Human Capital Efficiency, Structural Capital Efficiency, Capital Employed Efficiency, Market Performance.